Prarancangan Pabrik Fatty Alcohol Dari Cpo (Crude Palm Oil) Dengan Disain Alat Utama Menara Distilasi Methyl Ester - Panjaitan, Angga Marusaha Tamba; Rionaldo, Hari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Fatty Alcohol (fat alcohol) is a product of CPO processing. Fatty Alcohol is a derivative of vegetable fats and animal oils and is a non-oil and gas export commodity that is needed in various industries such as the perfume, cosmetics, pharmaceutical, food and beverage industries. The need for fatty alcohol continues to increase every year. The import of fatty alcohol has been carried out but the demand for fatty alcohol has not been met. this led to the establishment of a fatty alcohol factory with the main raw material being crude palm oil to cover this need. This factory was built with a capacity of 130,000 tons/year which will be established in Pelintung, Dumai. The fatty alcohol production process is carried out with 3 processes such as pretreatment, transesterification and hydrogenation. The main equipment design in this factory is fatty alcohol distillation which works to separate fatty alcohol as the top product from methyl ester as the base product. The feed, distillate and bottom temperatures in this distillation tower are 170 oC, 160.969 oC and 330.336 oC with a pressure of 1 atm. The fatty alcohol distillation has 11.225 m (441.929 in) high, 1,859 m (73.191 in) outside diameter, and uses skirt support. Economic analysis on the design of this plant shows that this plant is feasible to build with a factory Payback Period (PBP) of 0.93 years and BEP at a capacity of 20 %. Keywords:Crude palm oil, economic analysis, fatty alcohol, hydrogenation, transesterification,